Dampak Brand Extension terhadap Brand Personality (Studi Eksperimental pada Print Media Brand KOMPAS) - Sofyan, Muhammad Idham; Rahayu, Mintarti (Jurnal Aplikasi Manajemen, 2012)
The aim of this research is to know the difference of perception on KOMPAS brand personality; free-post the brand extension introduction. This explanatory research utilities in descriptive writing and applied experimental approach. This research design is a-within-subjects experimental design, in which the researcher compares two or more different treatment conditions (or compares treatment and control) by observing or measuring the same group of individuals in all of the treatment conditions being compared.Personality model is an approach to determine brand personality refering to the big five dimensions by Geuens, et. al (responsibility, activity, aggresiveness, simplicity, and emotionality). As a printed mediabrand, KOMPAS executly the brand development strategies by extending its brand to Kompas.com and KOMPAS TV which assumed it can change the major brand personality. The findings are: the composit forming to be 7 (seven) newly factors standing for brand personality KOMPAS (reliable, relevant, involve, up to date, representative, trustworthy, and emotionally touch); and the provided treatments significantly result on different changed perception of participants to examine the factors on KOMPAS brand personality with 10% level of significance. For the result, by extending its brand, the personality of KOMPAS changes.